DDS based MIL-STD-1553B Data Bus interface simulation. (April 2015) - Deniz, Ertan; Durak, Umut; Güçlü, Kadriye; Oguztuzun, Halit
This paper describes distributed simulation of MIL-STD-1553B Serial Data Bus interface and protocol based on the Data Distribution Service (DDS) middleware standard. The 1553 bus connects avionics system components, and transports information among them in an aircraft. It is important for system designers to be able to evaluate and verify their component interfaces early in the design phase. The 1553 data bus requires specialized hardware and wiring to operate; thus it is complicated and expensive to verify component interfaces. Therefore modeling the bus on commonly available hardware and networking infrastructure is desirable for early evaluation and verification of designed interfaces. The DDS middleware provides publish/subscribe based communications and facilitates the implementation of distributed systems by providing an abstraction layer over the networking interfaces of the operating systems. This work takes the advantage of the DDS middleware to implement an extensibility 1553 serial data bus simulation tool. The tool is verified using a case study involving a scenario based on the MIL-STD-1760 standard.